Growth, Survival and Feed Conversion Ratio of Tilapia (Oreochromis niloticus) Cultivated in an Aquaponic System - Priyanto, Rafi Afriand; Pande Gde Sasmita Julyantoro; Ni Putu Putri Wijayanti (Gema Agro, 2024)
This research aims to determine the growth, survival and feed conversion ratio of tilapia (Oreochromis niloticus) cultivated in an aquaponic system. The commodities used in this research were 200 tilapias (Oreochromis niloticus) with a size of ± 6 cm, water spinach (Ipomea aquatic), and pak choy (Brassica rapa L.). This research was conducted in the cultivation ponds of the Faculty of Marine Affairs and Fisheries, Udayana University. This research was conducted from April to May 2024. The method used was quantitative description. The average growth parameters from the results obtained were for the weight and length of tilapia fish at 10.54 g and 9.23 cm, the specific growth rate was 2%/day, survival was 83%, and the feed conversion ratio was 2,54. The water quality tested in this study was still adequate to support the growth of tilapia, namely for the temperature parameter of 29.14oC; DO of 5.22 mg/L; and pH of 6.96. Fish growth parameters such as weight, length, specific growth rate, and survival are classified as good, but the feed conversion ratio is quite high.